First principles study on interstitial C and substitutional Mn in bcc iron: structural stability and elastic properties. (May 2014) - Kou, B.; Kou, Z.; Liu, Y.; Han, P.
<x content-type="archive" xml:space="preserve">Abstract</x> We use advanced first principles calculation based on density functional theory to reveal the electrical structure and elastic property of bcc Fe–Mn–C alloys. Results indicate that the solid solution of interstitial C and substitutional Mn can enhance the stability of the Fe–Mn–C system. In addition, the solid solution of Mn has minimal influence on the system structure parameter and C promotes the increase of cell parameter along the c-axis direction. Further research on the mechanical property reveals that the solid solution of Mn and C could enhance the bulk modulus and the shear modulus of the Fe–Mn–C system. The phenomenon could be ascribed to the combination between atoms which is strengthened by the new bond peak that resulted from the solid solution of the Mn 3d and the C 2s and 2p orbits.